Comparative static and shaking culture of metabolite derived from methyl red degradation by Lysinibacillus fusiformis strain W1B6 - Sari, Ira Puspita; Simarani, Khanom (The Royal Society, 2019)
This paper reports on the comparative characteristics and properties of the metabolites derived from methyl red (MR) decolorization by Lysinibacillus fusiformis strain W1B6 under static and shaking conditions. A batch culture system was used to investigate the effect of aeration on azoreductase activity in the biodegradation process, transformation of colour removal and the metabolite products. Biodegradation analysis was monitored using Fourier transform infrared spectroscopy and high-performance liquid chromatography while metabolites were determined using gas chromatography- mass spectroscopy. Phytotoxicity and anti-microbial tests were also conducted to detect the toxicity of metabolites. The results showed that this strain grew more rapidly under shaking conditions while azoreductase activity increased more rapidly under static conditions. Despite that, no significant difference in the decolorization was observed under both static and shaking conditions with up to 96% and 93.6% decolorization achieved, respectively, within 4 h of incubation. MR was degraded into two fragmented compounds, i.e. 2-aminobenzoic acid and N,N-dimethyl-1.4-benzenediamine. The concentration of 2-amino benzoic acid was higher under static conditions resulting the biotransformation of 2-amino benzoic acid into methyl anthranilate more rapidly under static conditions. Other metabolites were also detected as intermediate biotransformation products and by-products. Less or no toxic effect was found in the metabolite degradation products under both culture conditions. © 2019 The Authors.